INFLUÊNCIA DA CURA ÚMIDA EM ARGAMASSAS ESTABILIZADAS - Melo, Fernanda; Kretzer, Rafael; Brito, Larissa; Casali, Juliana; Oliveira, Alexandre; Calçada, Luciana (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Ready mix mortar is characterized by remain the workability for extended periods. This characteristic is obtained by using air-entrained admixture and hydration stabilizing admixture. The hydration stabilizing admixture regulates C3S hydration resulting in a delay in start of the reactions. In firsts ages, the mortar is sensitive to climatic factors that may results in water lost by evaporation. In ready mix mortars, the loss of water before the start of the cement hydration reactions may lead to losses flexural tensile strength and compressive strength. In this context, the objective of this study was to evaluate the influence of wet curing in mortar specimens. In fresh state the tests were: consistency index, specific gravity and air entrained content. Specimens were formed and submitted to curing by immersion during three different periods of times. In the hardened state the specimens were analyzed with respect to flexural tensile strength and compressive strength. The results show that wet curing improve the studied properties in the hardened state, however they are not conclusive about the suitable period for the curing process.